An inductive discussion of the interrelationships between nursing shortage, horizontal violence, generational diversity, and healthy work environments - Francesca Armmer (Administrative Sciences, 2017)
The complex features of the nursing shortage, horizontal violence, generational diversity and healthy work environments have frequently been addressed within the context of their singular characteristics, challenges and potential solutions. Yet it is the interrelationships of these phenomena that holds solutions to the overarching challenges facing nurses and the nursing profession. Through an inductive approach, a preliminary discussion and related strategies to address the highlighted challenges have been proposed.
Keywords: 350; nursing shortage; horizontal violence; generational diversity; healthy work environments